BARRIERS TO MEDICATION ADHERENCE AMONG CARDIOVASCULAR DISEASE PATIENTS AND ASSESSMENT OF COMPLIANCE TOWARDS TREATMENT (The Research of Medical Science Review, 2025)
Background: Medication adherence refers to how well patients follow their prescribed treatment. In Pakistan, a survey revealed that 68.14% of patients do not take medications as directed, highlighting a serious issue that can negatively impact health outcomes. Objectives: To access the barriers towards medication adherence and evaluate the Compliance towards treatment among cardiovascular disease patientsMethod: A descriptive cross-sectional study was conducted in Sheikh Zaid hospital, Lahore and completed in 4 months. Convenient sampling technique was used with sample size of 138. A modified questionnaire was used for data collection and analyzed by Chi-Square test to find the significance between categorical variables.Result: The finding of this study concluded that most of the patients were male, having age between 51-65 years, primary level of education. Regarding to patients’ compliance toward treatment (67.39%) with good compliance, while (32.60%) participants with poor. There is a significant difference between the compliance level of all study participants with the p less than 0.06.Conclusion: According to this study majority of patients were with good compliance towards treatments. Furthermore, barriers that affect medication adherence in cardiovascular disease patients were forgetfulness and concern adverse reactions. Study suggested those who visited Shiekh Zayad hospital OPD should receive educational intervention and lifestyle modification.